Feasibility of electrical power generation using thermoelectric modules via solar pond heat extraction. (1st March 2017) - Ding, L.C.; Akbarzadeh, A.; Singh, B.; Remeli, M.F.
Highlights: The heat from solar pond was converted to electricity using thermoelectric modules. Different climatic conditions were considered in the feasibility analysis. The system's performances in both ideal and practical cases were discussed. Abstract: Solar pond undoubtedly has been a reliable source of low grade heat supply by acting as both collector and storage for the incoming solar radiation. The thermal efficiency of the solar ponds is between 15 and 25% of the incoming horizontal solar radiation. Meanwhile, the thermoelectric technology enables the conversion of heat into electricity using thermoelectric modules. In this paper, the feasibility of the system by combining solar pond and thermoelectric modules is presented. This system can be achieved by using a thermoelectric modules-embedded heat exchanger module that will able to extract the heat available from the lower convective zone of the solar pond. The analysis in this paper was conducted by investigating the solar ponds operating in different climate conditions, which are Group A (Kuala Lumpur), Group B (Riyadh) and Group C (Melbourne and Granada) base on Köppen climate classification. The theoretical feasibility draws the limit on the performance and cost of the solar pond-thermoelectric system under commercially available thermoelectric technology at the present state. Later, the result was contrasted against the performance of the power generation units operate under realisable operating condition with solar pond. The result in this study revealed that, under ideal condition, the system is at least 10 times costly compared to other renewable energy sources like off-grid solar photovoltaic system with storage. Meanwhile, at its best operating climate, this system will be able to achieve annual carbon dioxide reduction of 2.38 kg/m 2 -year in a practical case.